Arabidopsis rbcS genes are differentially regulated by light. - Dedonder, A (1993)
Individual members of the Arabidopsis thaliana ribulose-1,5-bisphosphate carboxylase/oxygenase small subunit (rbcS) gene family are differentially regulated by light of different qualities. In 10-d-old etiolated seedlings, the expression of only three of the four genes is under inductive phytochrome control. rbcS mRNA levels reach a maximum (3- to 5-fold higher than the dark level) about 6 h after a red light pulse, but the rate of decay differs among the genes. Moreover, rbcS 2B requires a higher fluence for induction. At early stages of development, rbcS 1A, 2B, and 3B are highly expressed in the dark and cannot be further induced by red light, indicating a developmental component in the overall regulatory mechanism. Continuous light experiments indicate that high-irradiance responses may play a role in the induction of at least three of the four rbcS genes. Under conditions of phytochrome saturation, rbcS 1A is insensitive to blue light pulses, whereas among the three B locus genes, at least rbcS 3B appears to respond to a blue-light photoreceptor. These results add to the data suggesting that individual members of rbcS gene families in higher plants may be subject to a variety of differing regulatory mechanisms.